2011
DOI: 10.1007/s00415-011-6109-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in untreated Parkinson’s disease

Abstract: Sleep abnormalities are frequently found in Parkinson's disease (PD). However, it is unclear if they are present from the initial stages of PD. We thus aimed to assess sleep disturbances in newly diagnosed PD patients. We investigated 20 untreated PD patients using the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI) and the PD Sleep Scale (PDSS). Video-polysomnography and multiple sleep latency test (MSLT) were performed in 15 patients and 15 healthy controls. The ESS score was abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 37 publications
4
42
1
1
Order By: Relevance
“…patients compared with controls was observed, whereas only one patient clinically manifested RBD [22]. Because RBD precedes the onset of PD and can manifest during the early phase of PD, abnormalities in REM sleep in the early phase of PD are supported by PSG findings.…”
Section: Rem Sleep Behavior Disordersupporting
confidence: 64%
See 2 more Smart Citations
“…patients compared with controls was observed, whereas only one patient clinically manifested RBD [22]. Because RBD precedes the onset of PD and can manifest during the early phase of PD, abnormalities in REM sleep in the early phase of PD are supported by PSG findings.…”
Section: Rem Sleep Behavior Disordersupporting
confidence: 64%
“…No differences in mean SL between the levodopa-alone group and the levodopa and dopamine agonist group were reported [20]. In untreated PD patients, the mean SL on MSLT was not different compared with controls (11.7±4 vs. 12.5±2 min) [22]. The mean SL was in the pathological range (<8 min) in three PD patients and in none of the controls, and one patient with PD had a single sleep onset REM on MSLT.…”
Section: Multiple Sleep Latency Testmentioning
confidence: 94%
See 1 more Smart Citation
“…With disease progression, EDS becomes very frequent and prominent [67], and the addition of dopaminergic medication appears to worsen its severity [66]. In early studies, subjective sleepiness and short sleep latencies in the multiple sleep latency test indicative of objective EDS were present in some drug-naïve patients with Parkinson's disease but not more often than in controls [68][69][70]. However, men with EDS had a three-fold higher risk of developing Parkinson's disease than controls without EDS [71].…”
Section: Excessive Daytime Sleepinessmentioning
confidence: 99%
“…18,19,21 With regard to the influence of dopaminergic medication, several studies have now shown that increased daytime sleepiness or a condition mimicking narcolepsy 22 develops after the introduction of dopaminergic treatment, particularly D3 agonists, in patients with PD, while there is no difference in prevalence of EDS in untreated patients with PD compared with healthy controls. [23][24][25] These studies indicate that dopaminergic therapy plays a strong role in the emergence of EDS in PD. EDS in patients with PD who have never used dopamine agonists was found to be associated with H&Y stage 23 and mood and autonomic dysfunction, 25 suggesting that disease-related changes in sleep-wake regulation also contribute to EDS.…”
mentioning
confidence: 85%